Abdominal pregnancy with live newborn - Falcón, Arlene (2015)
Abdominal pregnancy with live newborn is an exceptional ectopic pregnancy in human reproduction that usually is associated with high maternal and fetal mortality and morbidity. We report a case of a 34 weeks abdominal pregnancy with live newborn and review the literature and recall two other cases occurring in the Amazon region of Ucayali, Peru, during the last decade.